Severe Metabolic Acidemia in a Patient with Aleukemic Leukemia. (18th November 2018) - Ghrewati, Moutaz; Manji, Faiza; Modi, Varun; Chandran, Chandra; Maroules, Michael
Abstract : Malignancy associated lactic acidosis is a rare metabolic complication that may accompany various types of malignancies. To date, most cases that have been reported are associated with hematologic malignancies (lymphoma and leukemia). Many theories have been proposed to explain the pathophysiology of lactic acidosis in malignancies. We are reporting an unusual case of a 62-year-old female who presented with a complaint of generalized weakness. Patient was found to have pancytopenia and metabolic acidosis with an anion gap secondary to lactic acid in addition to non-anion gap acidosis (NAGA). The lactic acidosis resolved only after initiation of chemotherapy as she was diagnosed with B-cell acute lymphoblastic leukemia. Our patient also had a coexistent Renal Tubular Acidosis (RTA) with large kidneys. The kidney size also decreased with chemotherapy. Our case is unique as evidenced by aleukemic leukemia combined with anion gap acidosis and non-anion gap acidosis. Lactic acidosis has many different causes; although rare, hematologic malignancies should be included in the differential diagnosis regardless of cell counts or tumor burden.